ANALYSIS OF GENDER EQUALITY IN THE FILM BARBIE THE MOVIE - Alviyanti, Ika Fitri; Siraj, Fuad Mahbub (Al-Adyan: Journal of Religious Studies, 2023)
Gender-based discrimination still occurs in various aspects of life. In fact, currently gender equality has experienced extraordinary progress. The nature and severity of discrimination varies widely between countries and regions. Women do not enjoy equal access to political, social and economic rights in any country or region in the world. This research is qualitative research with the type of library research. This research seeks to understand how gender equality is represented in the Barbie film using descriptive analysis methods. The primary data source used in this research is the film Barbie The Movie. This primary source is in the form of scenes or images that show gender equality in the film Barbie The Movie. This data is obtained from the Loklok application. Later, relevant data will be collected and examined through an analysis process. The results of this research show how the Barbie film inspires women around the world and promotes gender equality. Through engaging storytelling, Barbie films inspire girls to recognize gender differences, believe in themselves, and achieve their goals. Diskriminasi berbasis gender masih terjadi di berbagai aspek kehidupan. Faktanya, saat ini kesetaraan gender telah mengalami kemajuan yang luar biasa. Sifat dan tingkat keparahan diskriminasi sangat bervariasi antar negara dan wilayah. Perempuan tidak menikmati akses yang sama terhadap hak-hak politik, sosial dan ekonomi di negara atau wilayah mana pun di dunia. Penelitian ini merupakan penelitian kualitatif dengan jenis penelitian kepustakaan. Penelitian ini berupaya memahami bagaimana kesetaraan gender direpresentasikan dalam film Barbie dengan menggunakan metode analisis deskriptif. Sumber data primer yang digunakan dalam penelitian ini adalah film Barbie The Movie. Sumber primer ini berupa adegan atau gambar yang menampilkan kesetaraan gender dalam film Barbie The Movie. Data ini didapat dari aplikasi Loklok. Nantinya, data yang relevan akan dikumpulkan dan diperiksa melalui proses analisis. Hasil penelitian ini menunjukkan bagaimana film Barbie menginspirasi perempuan di seluruh dunia dan mempromosikan kesetaraan gender. Melalui penyampaian cerita yang menarik, film Barbie menginspirasi anak perempuan untuk mengenali perbedaan gender, percaya pada diri sendiri, dan mencapai tujuan mereka.